Popular music as promotion music and branding in the digital age - Meier, Leslie M. (Polity Press, 2017)
Business-as-usual has been transformed across the music industries in the post-CD age. Against widespread hype about the purported decline of the major music labels, this book provides a critique of the ways these companies have successfully adapted to digital challenges, and what is at stake for music makers and for culture. Today, recording artists are positioned as artist-brands and popular music as a product to be licensed by consumer and media brands. Leslie M. Meier examines key consequences of shifting business models, marketing strategies, and the new common sense in the music industries: the gatekeeping and colonization of popular music by brands.